Agglomerated serum albumin adsorbed protocatechuic acid coated superparamagnetic iron oxide nanoparticles as a theranostic agent - Bozoglu, Serdar; Arvas, Melih Besir; Varli, Hanife Sevgi; Ucar, Burcu; Acar, Tayfun; Karatepe, Nilgun (IOP Publishing Ltd, 2023)
Iron oxide nanoparticles have been one of the most widely used nanomaterials in biomedical applications. However, the incomplete understanding of the toxicity mechanisms limits their use in diagnosis and treatment processes. Many parameters are associated with their toxicity such as size, surface modification, solubility, concentration and immunogenicity. Further research needs to be done to address toxicity-related concerns and to increase its effectiveness in various applications. Herein, colloidally stable nanoparticles were prepared by coating magnetic iron oxide nanoparticles (MIONPs) with protocatechuic acid (PCA) which served as a stabilizer and a linkage for a further functional layer. A new perfusion agent with magnetic imaging capability was produced by the adsorption of biocompatible passivating agent macro-aggregated albumin (MAA) on the PCA-coated MIONPs. PCA-coated MIONPs were investigated using infrared spectroscopy, thermogravimetric analysis and dynamic light scattering while adsorption of MAA was analysed by transmission electron microscopy, Fourier-transform infrared spectroscopy and x-ray diffraction methods. Magnetic measurements of samples indicated that all samples showed superparamagnetic behaviour. Cytotoxicity results revealed that the adsorption of MAA onto PCA-coated MIONPs provided an advantage by diminishing their toxicity against the L929 mouse fibroblast cell line compared to bare Fe3O4.
Keywords: magnetic nanoparticles; cytotoxicity; surface coatings; nanoparticle stability; perfusion; HIGH SATURATION MAGNETIZATION; OLEIC-ACID; MAGNETITE NANOPARTICLES; FE3O4 NANOPARTICLES; PULMONARY-EMBOLISM; CANCER; HYPERTHERMIA; DIAGNOSIS; DELIVERY; Science & Technology - Other Topics; Materials Science; Physics